A Critical Assessment on Nepal’s Journey to Socialism - Chaulagain, Sangam (International Research Journal of MMC, 2021)
This article makes a critical assessment on Nepal’s journey to socialism. Nepal, through its constitution, has formally promised to lead the eco-politics of this country to the path of socialism. This article discusses the current initiatives that have been taken by the state after the constitution of 2015 formally announced socialism as the guiding eco-political principle of the nation. This article has been prepared on the basis of qualitative research through the secondary information collected from various sources. Although a formal promise has been made for socialism in the constitution, Nepal is highly influenced by capitalist system, and the rulers are under the clutch of neo-liberalism. The documents of major political parties show that they are trying to move forward in the path of social democracy, but they need to make radical corrections in their practical behaviors and performances to establish socialist eco-political culture in Nepal.